Analisis Pendapatan Kelayakan Usahatani Cabai Rawit Merah (Capsicum Frutescens L) Di Kecamatan Ngablak Kabupaetn Magelang - Reza Subastian; Yuliawati Yuliawati (Jurnal Agribisnis Indonesia, 2024)
Red cayenne pepper is a horticultural commodity that is a priority for the government's development at this time because it has a high economic value and has the potential to be developed. In March 2023 there was a volcanic ash eruption of Mount Merapi which had an impact on reducing the productivity and quality of red cayenne pepper. Sumberejo Village is one of the areas in Ngablak Subdistrict that conducts red bird's eye chili farming and is affected by the volcanic eruption. This research intends to evaluate chili farming after the eruption of Mount Merapi, which had a negative impact. Thus, this study aims to analyze the revenue, costs, and income, as well as the feasibility of cayenne pepper farming in Sumberejo Village, Ngablak sub-district, Magelang District. The type of research used is Descriptive quantitative. The sampling technique was done by purposive sampling with a total sample of 17 respondents. Data collection was done by interview. Data analysis techniques used are revenue analysis, costs, income, R / C Ratio, B / C Ratio, production BEP and price BEP. The results showed that cayenne pepper farming in Sumberejo Village provided revenue of Rp 93,471,342, -/ha/season, total costs of Rp 56,986,742, -/ha/season with the largest cost being fertilizer costs (27.47%), and income of Rp 36,484,600, -/ha/season. The feasibility of farming based on R/C Ratio is 1.64, B/C Ratio is 0.64, while the production BEP is 2,750.9 kg/ha and the price BEP value is Rp 10,130/kg. Based on the results of the study, it is concluded that despite being affected by the Merapi volcanic eruption, red bird's eye chili farming in Sumberejo Village still provides positive income and feasible to cultivate.